Metabolite analysis of Aspergillus fumigatus conidial supernatant and its pro-inflammatory activity in vitro and in vivo - Li, Qiujie; Li, Shan; Kang, Yuting; Xue, Jian; Wang, Pengtao; Jia, Wei (Frontiers in Immunology, 2026)
IntroductionAspergillus fumigatus (A. fumigatus) conidia have been reported to induce inflammatory response in macrophages, resulting in lung damage. However, the role of secondary metabolites secreted by conidia during the infection process remains unclear. Our objective is to investigate the metabolic changes produced by conidia at different developmental stages and to assess the effects of the conidial supernatant on the inflammatory response of macrophages.MethodsWe employed optical microscopy, electron microscopy, and nuclear division staining to identify the morphological characteristics of the Aspergillus fumigatus strain Af293 conidia at various developmental stages. Metabolomic analysis of the supernatant from conidial pre-germination (Af293-4h) and post-germination (Af293-12h) was performed using Liquid Chromatography-Mass Spectrometry. Conidial supernatant was utilized to stimulate mouse alveolar macrophages (MH-S) cells, and the expression of inflammatory factors was quantified using ELISA and RT-qPCR. Western blotting was conducted to detect the levels of key proteins involved in the inflammatory pathway. Furthermore, mice were administered an intranasal instillation of the supernatant to construct the pneumonia model, and lung pathology was evaluated through hematoxylin-eosin (HE) staining, while the levels of inflammatory factors in bronchoalveolar lavage fluid were assessed using ELISA and RT-qPCR.ResultsNon-targeted metabolomics analyses reveal an increased secretion of organic acids and their derivatives, lipids and lipid-like molecules, phenolic compounds, phenylpropanoids, polyketides, as well as alkaloids and their derivatives following conidial germination. Compared to Af293-4h supernatant, Af293-12h supernatant induce a significantly stronger inflammatory response in MH-S cells, characterized by the increased expression of inflammatory factors, including IL-1β, TNF-α, CCL/CXCL and MMPs, via the activation of JAK/STAT/AKT and MAPK signaling pathways. Nasal exposure of conidial supernatant in mice can induce lung inflammation, resulting in lung damage and an elevated proportion of inflammatory cells, as well as increased levels of the inflammatory factors such as TNF-α, IL-1β, and IL-6.ConclusionOur research indicates significant differences in the metabolites of A. fumigatus conidial supernatant between the pre-germination and post-germination stages. The conidial supernatant can induce a pronounced inflammatory response in macrophages, mediated by the activation of the JAK/STAT/MAPK pathways. Long-term exposure to spore supernatant in mice can result in pneumonia and tissue damage.